Assessment of fiscal effort and voluntary tax compliance in Peru - Ramirez Zamudio, Aldo Fabricio (2020)
This study examines the fiscal effort and voluntary compliance in the payment of taxes in Peru, given that in 2014, the Peruvian economy collected only 52.8% of its total tax potential. Through an experiment, the research shows that dissuasive policies only do not explain the whole phenomenon of tax compliance; on the contrary, some psychological factors, denoted in the literature as “tax morale”, should also be considered in such study. Thus, if Peru expects to join the OECD (a goal for celebrating the bicentennial of its independence), it must improve tax compliance to standards equal to those of more developed countries; some non-dissuasive and low-cost public policies based on tax morale research may help to achieve this goal.